How much the swimming performance leading to Tokyo 2020 olympic games was impaired due to the Covid-19 lockdown? - Costa, M. J.; Garrido, N. D.; Marinho, D. A.; Santos, C. C. (Journal of Sports Science & Medicine, 2021)
The aim of this study was to analyze the progression and stability in the performance of world-ranked swimmers from 2015 to 2020, and the impairment induced by the COVID-19 lockdown. An observational retrospective design over five consecutive competitive seasons was selected. FINA`s male Top-50 who were qualified for the Tokyo Olympic Games were considered in freestyle, backstroke, backstroke, and butterfly events. A total of 515 male swimmers and 2060 season-best performances were analyzed. All data was retrieved from two open-access and public websites (Swimrankings and Swimcloud). Repeated measures ANOVA followed by the Bonferroni post-hoc test was performed to analyze the variation between seasons. Stabilization in performance was assessed using spearman correlation coefficients. A significant improvement in performance ˜0.5-2.5% was found in most of the strokes and race distances until the 2018-2019 season. The 2020 lockdown impaired the performance by 1-2%. Moderate to high associations were found in the 2017-2018 season when considering the 2019-2020 performance. The breaststroke was the only stroke with a moderate-high stability (r > 0.40) in all race distances considering the overall time period. It can be concluded that world-ranked swimmers` performance was impaired by 1-2% due to the COVID-19 lockdown, returning to levels that were reached two years earlier.